Performance Simulation of a Free Piston Linear Generator by Using MATLAB Simulink - Mohamed Asri, Mohamad Aimran (IRC, 2021)
Free piston linear generator (FPLG) is a crankless two-strokes engine that uses heat energy and convert it to electrical energy by electromagnetic induction, via the reciprocation of the FPLG piston linear motion.